2021
DOI: 10.3390/insects12040298
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Push–Pull Systems to Fall Armyworm (Spodoptera frugiperda) Management in Maize Crops in Morelos, Mexico

Abstract: Chemical control is the main method used to combat fall armyworm in maize crops. However, its indiscriminate use usually leads to a more complex scenario characterized by loss of its effectiveness due to the development of resistance of the insect pest, emergence of secondary pests, and reduction of the populations of natural enemies. For this reason, efforts to develop strategies for agroecological pest management such as Push–Pull are increasingly growing. In this context, the present study was carried out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Similar observations were made by Hailu et al [ 18 ] on maize–legume intercrops in Uganda compared to maize monoculture. Guera et al [ 38 ] demonstrated that maize push–pull cropping systems encompassing Brachiaria hybrid cv. Mulato II, Panicum maximum Jacq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations were made by Hailu et al [ 18 ] on maize–legume intercrops in Uganda compared to maize monoculture. Guera et al [ 38 ] demonstrated that maize push–pull cropping systems encompassing Brachiaria hybrid cv. Mulato II, Panicum maximum Jacq.…”
Section: Discussionmentioning
confidence: 99%
“…Although these weeds may also host FAW’s natural enemies [ 55 ], they may also host other pests, including cereal stemborers with which FAW share the same ecological niche and may contribute to the damage inflicted on the maize plants [ 56 , 57 ]. If weeds, including the gramineous ones, which are closely related to maize, attract FAW, it will be advantageous to plant them around the maize field to attract FAW away from the maize, such as in the push–pull strategies that have been developed for stemborers [ 38 ]. This is one of the key principles utilized by push–pull companion cropping against stemborers by using Napier grass as a trap crop, as it is more attractive to the ovipositing females [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study was conducted in the mosaic of agroecosystems established in the field effectiveness evaluation experiment conducted by Guera et al (2021) in an area located between coordinates 18.893323N and 99.102158W. This mosaic consists of the treatments evaluated in the experiment (Table 1): m onocultures (negative control) and nine push-pull systems proposed by Guera et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…The data were obtained from an experiment established following a randomized block design. In this experiment, monocultures and nine push-pull systems (ten management systems) proposed by Guera et al (2020) were evaluated in 3 blocks, totaling 30 experimental units (plots) of size 14m × 14m (Guera et al, 2021;Guera et al, 2023). The evaluated push-pull systems were: 1) Brachiaria hybrid cv Mulato II -Dysphania ambrosioides (MIID), 2) Brachiaria hybrid cv Mulato II -Crotalaria juncea (MIIC), 3) Brachiaria hybrid cv Mulato II -Tagetes erecta (MIIT), 4) Panicum maximum cv Tanzania -Dysphania ambrosioides (TD), 5) Panicum maximum cv Tanzania -Crotalaria juncea (TC), 6) Panicum maximum cv Tanzania -Tagetes erecta (TT), 7) Panicum maximum cv Mombasa -Dysphania ambrosioides (MD), 8) Panicum maximum cv Mombasa -Crotalaria juncea (MC), 9) Panicum maximum cv Mombasa -Tagetes erecta (MT).…”
Section: Data Collectionmentioning
confidence: 99%